Regarding “Effectiveness and Persistence of Anti-TNFα Treatment in Patients with Rheumatoid Arthritis - A 7 Years Real-World Cohort Study” [Letter] - Borrás-Blasco J; Valcuende-Rosique A; Cornejo-Uixeda S (Biologics: Targets & Therapy, 2025)
Joaquín Borrás-Blasco,1 Alejandro Valcuende-Rosique,2 Silvia Cornejo-Uixeda1 1Pharmacy Department, Sagunto Hospital, Sagunto, Spain; 2Pharmacy Department, Alzira Hospital, Sagunto, SpainCorrespondence: Joaquín Borrás-Blasco, Pharmacy Department. Hospital de Sagunto, Avda Ramon y Cajal s/n, Sagunto, Valencia, 46520, Spain, Tel +34 962339435, Fax +34 962659428, Email jborrasb@gmail.com